Pelaksanaan Program One Day One Juz oleh Siswa di SMK Plus Perbankan Bougenville Kec. Lubuk Basung Kab. Agam - Fitriani, Reza; Hasnah, Nur (Yayasan Daarul Huda Kruengmane, 2025)
The Qur'an as the holy book of Muslims will be used as a guide for human life. Reading the Qur'an should not be just reading, but there are rules that will be needed in reading the Qur'an. Reading the Qur'an has the value of worship in the sight of ALLAH. As Muslims we must love the Qur'an by reading and studying it. SMK Plus Perbankan Bougenville is one of the schools that will implement reading the Qur'an routinely and targeting to complete it every month. This one day one juz program was formed to accommodate and facilitate and make it easier for Muslims to get used to reading the Qur'an one day one juz, and to create students who will love the Qur'an. This study aims to determine the uniqueness of the implementation of the one day one juz program in this vocational school. Collection of observation data, interviews, and documentation. Data analysis through data reduction, presentation, drawing conclusions. This study concludes the implementation of the one day one juz program at SMK Plus Banking Bougenville, namely: reading the Qur'an one day one juz at this school is carried out together by all students of SMK Plus Banking Bougenville in the school prayer room, namely at 6:30 to 7:30, reciting the Koran in the morning is mandatory and if there are students who do not recite the Koran, they will be punished. In its implementation, it can be said that it has gone completely well, and has reached a 75% success rate for this program.